Government Policy on Higher Education: An Analysis of the Merdeka Belajar-Kampus Merdeka Policy: (Kebijakan Pemerintah dalam Pendidikan Tinggi: Analisis Kebijakan Merdeka Belajar-Kampus Merdeka) - Muhammad Taisir; Muhammad MS (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2024)
This paper discusses the government's policy on Higher Education, which is related to the Free Learning-Free Campus policy issued by the Ministry of Education and Culture under the chairmanship of Minister Nadim Makarim. This policy contains four main policies, namely facilitating the opening of new study programs, changing the higher education accreditation system, facilitating universities to become legal entities, and the right to study three semesters outside the study program. Although these policies substantially aim to improve the quality of education in Indonesia, on the other hand, it inevitably creates pros and cons. Some are optimistic but some are pessimistic.